Iodine-Rich Nanoadjuvants for CT Imaging–Guided Photodynamic Immunotherapy of Breast Cancer - Xin, Xiaoyan; Ni, Xiaoyue; Shi, Kang; Shao, Jie; Zhang, Yanqiu; Peng, Xin; Yang, Wen; Tian, Chuanshuai; Zhou, Wen; Zhang, Bing (Frontiers in Bioengineering and Biotechnology, 2022)
Immunotherapy which stimulates body’s own immune system to kill cancer cells has shown great promise in the field of cancer therapy. However, the uncontrolled biodistribution of immunotherapeutic drugs may cause severe side effect. Herein, we report an iodine-rich nanoadjuvant (INA) for photo-immunotherapy. INA is prepared by encapsulating a toll-like receptor 7 agonist (R837) and a photosensitizer (phthalocyanine) into an iodine-rich amphiphilic copolymer PEG-PHEMA-I. By virtue of the enhanced permeation and retention (EPR) effect, INA can effectively accumulate into tumor site. Under light irradiation, photodynamic therapy (PDT) triggered by INA will induce immunogenic cell death (ICD) in the tumor region to trigger the release of immune-associated cytokines. Such process may further induce the maturation of dendritic cells which will be accelerated by R837, leading to the proliferation of effector T cells for immunotherapy. The photo-immunotherapy mediated by INA shows good anticancer efficacy both in vitro and in vivo. Meanwhile, INA is also a CT contrast agent owing to its high density of iodine, which can successfully light up tumor by CT imaging. Thus, our study develops a light triggered nanoadjuvant for CT imaging-guided enhanced photo-immunotherapy.